Elimination and Quantification of Oxidation Induced Interstitial Injection via Ge Implants. (25th April 2017) - Martin, Thomas P; Jones, Kevin Scott; Camillo-Castillo, Renata A; Hatem, Chris; Xin, Yan; Elliman, Robert G
Abstract : The presence of Silicon-Germanium (SiGe) alloys at the Si/SiO2 interface during oxidation is known to suppress the injection of silicon self-interstitials that normally accompanies silicon oxidation and lead to observed effects such as Oxidation Enhanced Diffusion (OED) and stacking fault growth. This study uses a layer of implantation induced dislocation loops to measure interstitial injection as a function of SiGe layer thickness. The loops were introduced by implanting phosphorus and thermal annealing, and Germanium was subsequently introduced via a second implant at 3 keV over a range of doses between 1.7 x10 14 cm -2 and 1.4 x10 15 cm -2 . Results show that partial suppression of interstitial injection can be observed for sub-monolayer doses of germanium, and that more than three monolayers of SiGe are necessary to fully suppress interstitial injection below our detection limit during oxidation. They further show that low energy implantation of germanium opens up possibilities to eliminate or modulate injection of interstitials during thermal processing of future devices.